Role of discrete nature of chip formation and natural vibration of system components in chatter formation during metal cutting - Amin, A. K. M. Nurul; Jaafar, Israd Hakim; Patwari, Muhammed Anayet Ullah; Zubaire, W. W. D. (IIUM Press, 2010)
In the present work a review of the existing theories of chatter formation has been conducted and the weaknesses of the most widely accepted ‘Regenerative Chatter theory’ in explaining various phenomena related to chatter formation have been identified. An attempt has been made in this work to determine the common causes of chatter formation in different metal cutting operations, namely, turning, thread cutting and end milling conducted on plain carbon steel AISI 1040. Experimental investigations have been conducted during the above types of machining processes to identify the marks of instability and chatter on the formed chips. It has been identified that in all the three machining operations the chips formed show a common type of discreteness in the form of secondary saw teeth, which appear at the free edge of the chip. Mechanism of formation of these teeth has been studied and the frequencies of their formation have been determined for different cutting conditions. Apart from the secondary saw teeth primary saw teeth have also been identified at the main section of the chip and their frequencies were also determined. At the same time the natural vibrations of the main system components have been identified and the acceleration amplitudes at the prominent natural frequencies during actual machining were recoded using a dedicated vibration monitoring system. The frequencies of secondary chip serration and the natural frequencies of the system components were plotted against cutting speed. Acceleration amplitudes at the prominent natural frequencies were also plotted separately against cutting force. Based on comparison and analysis of these two frequency and amplitude graphs it was concluded that chatter (vibration with relatively high amplitude) appears in the system when the frequency of secondary saw teeth approaches values equal to half or integer multiple of a prominent natural frequency of the system resulting in resonance. In the case of thread cutting and turning the main vibrating component was identified as the tool holder and in the case of end milling the main vibrating components were the tool holder and the spindle. Severe vibration/chatter was found to appear during end milling when the tool and the spindle simultaneously entered into resonance. This occurred when the chip serration frequency got close to the spindle’s natural frequency, which was approximately twice the value of the natural frequency of the tool holder in the conducted experiments.